Pengaturan Hukum Perlindungan Tumbuhan Pada Wilayah Pertambangan oleh Pemegang Izin Usaha Pertambangan (IUP) - Billy Brillyan Dwi Saputra; Sapto Hermawan; Fatma Ulfatun Najicha (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Indonesia is one of the world's megabiodiversity countries, with a high level of biodiversity, including various endemic plant species that play a crucial role in ecosystems. However, uncontrolled mining exploration poses a serious threat to biodiversity conservation, particularly for plant species that lack legal protection. Exploration activities can lead to habitat degradation, landscape changes, and disruption of pre-mining ecosystems. Normatively, Indonesian regulations govern environmental protection in the mining sector, yet they do not explicitly require holders of Exploration Mining Business Licenses (IUP Exploration) to conduct conservation efforts for affected plant species. Consequently, there is no adequate mitigation mechanism at the exploration stage. This study employs a normative juridical method with a literature study approach to analyze existing regulations and identify legal gaps related to plant conservation in pre-mining areas. The findings indicate the need for more comprehensive policies, including the implementation of ex-situ conservation and vegetation mapping prior to exploration. Strengthening regulations and strict supervision are strategic steps to maintain ecosystem balance and support sustainable mining practices.